The Harmonization of Wasathiyatul Islam: Transforming Values of Religious Moderation in the Dialectics of Indonesian Society - Tamam, Asep Majidi; Supardi, Adi; Erihadiana, Mohamad; Mardani, Dadan (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
The relationship between religious doctrine and national identity remains a critical discourse in the Muslim world. The object of this research is Wasathiyatul Islam (Islamic Moderation) in Indonesia, which serves as a theological framework for balancing religious observance with social justice. However, the emergence of rigid transnational ideologies poses a significant challenge to this harmony, creating a potential disconnect between religious doctrine and local culture. To address this issue, this research aims to analyze how the values of Wasathiyatul Islam are transformed and harmonized within the dialectics of Indonesian society. The study employs a descriptive qualitative method with a phenomenological approach. Data were collected through literature reviews and social observations, then analyzed using an interactive model to interpret the